Tau-tubulin kinase - Ikezu, Seiko; Ikezu, Tsuneya (Frontiers in Molecular Neuroscience, 2014)
Tau-tubulin kinase (TTBK) belongs to casein kinase superfamily and can phosphorylate microtubule-associated protein tau and tubulin. TTBK has two isoforms, TTBK1 and TTBK2, which contain highly homologous catalytic domains but their non-catalytic domains are distinctly different. TTBK1 is expressed specifically in the central nervous system and is involved in phosphorylation and aggregation of tau. TTBK2 is ubiquitously expressed in multiple tissues and genetically linked to spinocerebellar ataxia type 11. TTBK1 directly phosphorylates tau protein, especially at Ser422, and also activates cycline-dependent kinase 5 in a unique mechanism. TTBK1 protein expression is significantly elevated in Alzheimer’s disease brains, and genetic variations of the TTBK1 gene are associated with late-onset Alzheimer’s disease in two cohorts of Chinese and Spanish populations. TTBK1 transgenic mice harboring the entire 55-kilobase genomic sequence of human TTBK1 show progression of tau accumulation, neuroinflammation, and neurodegeneration when crossed with tau mutant mice. Our recent study shows that there is a striking switch in mononuclear phagocyte and activation phenotypes in the anterior horn of the spinal cord from alternatively activated (M2-skewed) microglia to pro-inflammatory (M1-skewed) infiltrating peripheral monocytes in P301L tau mutant mice by crossing with TTBK1 transgenic mice. TTBK1 is responsible for mediating M1-activated microglia-induced neurotoxicity, and its overexpression induces axonal degeneration in vitro. These studies suggest that TTBK1 is an important molecule for the inflammatory axonal degeneration, which may be relevant to the pathobiology of tauopathy including Alzheimer’s disease.